2008
DOI: 10.1016/j.nbd.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

LRP promotes endocytosis and degradation, but not transcytosis, of the amyloid-β peptide in a blood–brain barrier in vitro model

Abstract: The pathogenesis of Alzheimer's disease is characterized by aggregation of the amyloid-β protein (Aβ) into neurotoxic plaques. Recent in vivo studies have suggested the non-proteolytic clearance of Aβ via receptor-mediated transport across the blood-brain barrier (BBB). The aim of this study was to investigate the role of p-glycoprotein (Pgp) and the low-density lipoprotein receptor-related protein (LRP) in Aβ efflux across the BBB. We developed an in vitro BBB-like model using Madin Darby Canine Kidney (MDCK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 27 publications
(29 reference statements)
6
80
0
Order By: Relevance
“…LLC-MDR1 cells have enhanced basolateral-to-apical, but not apical-to-basolateral, permeability to FITC-Ab 1-40/42 (5 mmol/L, 1 h) compared with wild-type LLC cells, which was inhibited by 10 mmol/L of cyclosporin A (Kuhnke et al, 2007). In contrast, the basolateral-to-apical permeability of MDCK-MDR1 (Madin-Darby canine kidney epithelial cells overexpressing human MDR1) is not increased compared with wild-type MDCK cells after incubation with 1 nmol/L of 125 I Ab 1-40 for 24 and 48 h (Nazer et al, 2008). These apparently contradicting results may reflect differences in the plasma membrane distribution of efflux transporters between different cultured epithelial cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…LLC-MDR1 cells have enhanced basolateral-to-apical, but not apical-to-basolateral, permeability to FITC-Ab 1-40/42 (5 mmol/L, 1 h) compared with wild-type LLC cells, which was inhibited by 10 mmol/L of cyclosporin A (Kuhnke et al, 2007). In contrast, the basolateral-to-apical permeability of MDCK-MDR1 (Madin-Darby canine kidney epithelial cells overexpressing human MDR1) is not increased compared with wild-type MDCK cells after incubation with 1 nmol/L of 125 I Ab 1-40 for 24 and 48 h (Nazer et al, 2008). These apparently contradicting results may reflect differences in the plasma membrane distribution of efflux transporters between different cultured epithelial cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…However, there are conflicting studies showing no or little contribution of LRP1 to Aβ clearance across the BBB (5,(17)(18)(19)(20). Due to the lack of appropriate model systems, the role of LRP1 at the BBB and the overall relevance of BBB clearance are insufficiently understood and debated (4,7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an in vitro model of polarized epithelial cells (MDCK) transfected with ABCB1, Aβ transport from the basolateral to the apical compartment was very low and was not altered by ABCB1 inhibition when compared to wild type control cells. 60 The authors concluded overexpression of ABCB1 does not promote Aβ clearance. 60 Furthermore, in an in vivo study using rats, the preadministration of quinidine or verapamil, ABCB1 inhibitors, to the rat brain did not significantly affect Aβ clearance.…”
mentioning
confidence: 99%
“…60 The authors concluded overexpression of ABCB1 does not promote Aβ clearance. 60 Furthermore, in an in vivo study using rats, the preadministration of quinidine or verapamil, ABCB1 inhibitors, to the rat brain did not significantly affect Aβ clearance. 61 This result was supported by an in vitro transport study where addition of the ABCB1 inhibitors tariquidar or vinblastine did not affect the brain-to-blood transport of 125 I-Aβ 40 ; however, both inhibitors facilitated blood-to-brain transport of 125 I-Aβ 40 , which suggests the minor or lack of ABCB1 contribution to Aβ clearance from the brain and emphasizes ABCB1 role in limiting Aβ access to the brain.…”
mentioning
confidence: 99%